2013
DOI: 10.1186/1756-6614-6-13
|View full text |Cite
|
Sign up to set email alerts
|

Reference interval of thyroid stimulating hormone and free thyroxine in a reference population over 60 years old and in very old subjects (over 80 years): comparison to young subjects

Abstract: BackgroundStudies based on laboratory data about thyroid stimulating hormone (TSH) and free thyroxine (FT4) reference interval (RI) show conflicting results regarding the importance of using specific values by age groups with advancing age. Retrospective laboratory data or non-specific criteria in the selection of subjects to be studied may be factors leading to no clear conclusions. The aim of this study is to test the hypothesis that TSH and FT4 have specific RI for subjects over 60 to 80 years.MethodsWe eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 35 publications
0
38
0
3
Order By: Relevance
“…Decreasing fT 4 concentrations were also noted in aging men [11] . Under T 4 treatment, TT 4 , fT 4 and fT 3 concentrations increased in young and old mice to comparable values.…”
Section: Discussionmentioning
confidence: 81%
“…Decreasing fT 4 concentrations were also noted in aging men [11] . Under T 4 treatment, TT 4 , fT 4 and fT 3 concentrations increased in young and old mice to comparable values.…”
Section: Discussionmentioning
confidence: 81%
“…This is the largest Brazilian study evaluating TSH concentrations in healthy pregnant women, in which the number of participants was much higher than that recommended by the NACB (7), selection was performed rigorously (clinical and TPOAb), including potentially interfering obstetric conditions (5), and the samples were adequately obtained (after fasting and in the morning in all participants). Ultrasonography (US) was not performed because of the following reasons: (i) US is not required by the National Academy of Clinical Biochemistry [NACB (7)]; (ii) studies have shown no change in the reference limits of normal TSH when subjects with ultrasonographic anomalies were excluded from the initial sample (10)(11)(12)(13)(14), a finding also demonstrated in a previous study from our group (15); (iii) no consensus exists regarding the ultrasonographic findings to be considered (10)(11)(12)(13)(14), and (iv) many of the subjects with US suggestive of chronic thyroiditis without circulating TPOAb are identified based on a personal history of autoimmune disease, a family history of thyroid disease or presence of goiter, which were exclusion criteria in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Serum TSH concentrations were measured by an immunometric method. The reference intervals of TSH were specific for each age group based on recent studies, which showed that TSH increases progressively and significantly with age [19-24]. The reference intervals for each age group were as follows: 6–14 years: 0.3–4.2 mU/L; 15–60 years: 0.3–4.3 mUL; 61–79 years: 0.4–5.8 mU/L; > 80 years: 0.4–6.7 mU/L.…”
Section: Methodsmentioning
confidence: 99%